Secularization as the objectification of F. Nietzsche's futurological ideas - Mudrakov, Vitaliy Viktorovych (Ukrai͏̈ns'ke relihijeznavstvo, 2017)
The article interprets the modern transformations in world view as the Nietzsche’s philosophic historical predictions. The author analyses, in particular, the changes features, mental and value perspectives of modern human determined by secularization processes. It is proved that F. Nietzsche’s philosophy has important prognostic potential with great theoretical and social topicality.